A new species of Petalobrissus Lambert 1916 (Echinoidea: Faujasiidae) from the Jandaíra Formation, Potiguar Basin (Brazil) - Alves, Jessika; Monteiro, Felipe A. C.; Matthews-Cascon, Helena; Johnsson, Rodrigo; Neves, Elizabeth G. (Zootaxa, 2018)
A new Late Cretaceous species of Petalobrissus, Petalobrissus lehugueurae sp. nov., is described from the Jandaíra Formation, Potiguar Basin, state of Rio Grande do Norte. To date, this genus comprises a total of 20 species, only two of which, Petalobrissus setifensis and Petalobrissus cubensis have so far been recorded from the Jandaíra Formation. Petalobrissus lehugeurae sp. nov. is distinguished from its congeners in that gonopores occupy only a small portion of the genital plates, in having a slit-like periproct and a unique abrupt depression of the test that forms a pronounced keel below the periproct. In addition, an identification key to species of Petalobrissus is presented.